Correlation of convective heat transfer for laminar conditions on hexagonal sub-channel in bandung TRIGA research reactor using computational fluid dynamics - Umar, Efrizon; Tandian, Nathanael Panagung; Septilarso, Anggoro; Azmairit, Aziz; Ramadhan, Anwar Ilmar; Wan Hamzah, Azmi
The forced convective heat transfer in hexagonal vertical sub-channels has been carried out using computational fluid dynamics (CFD). The size and geometry of the hexagonal used in the research specifically replicate the fuel element arrangement of the Bandung TRIGA research reactor. The main objective of this research is to develop new correlations to predict convective heat transfer coefficients in developing regimes or laminar flow regimes in sub-channels, especially for Reynolds numbers ranging from 260 to 1,500. The correlation equation from this research has been compared to the correlation equation for the square sub-channel resulting from previous research. There are small differences, which are predicted to be caused by differences in model geometry. The simulation was done for various heat fluxes in the heater surface. It varied from 100 W/m2to 25,000 W/m2with an increase of (500-5,000) W/m2intervals. Based on the analysis results, a new correlation equation is proposed in the form of Nu = 1.73(Gz)0.339and applies in the range for Graetz numbers75 ≤ Gz≤ 15,400.